Removal of Humic Acid from Aqueous Solution by Dimethyl Diallyl Ammonium Chloride and Acrylamide - Zhang, Peng; Ren, Bozhi; Zhou, Yi; Liu, Kejia (Asian Journal of Chemistry, 2013)
The removal of organic pollutant humic acid from aqueous solution by flocculants were investigated. Two kinds of inorganic flocculants polyaluminium chloride, polymeric ferric sulfate and two kinds of organic flocculants polydimethyl diallyl ammonium chloride, dimethyl diallyl ammonium chloride and acrylamide (PDA) were used, the PDA had the best effect. Then the single influential factor such as: the dosage of the flocculants, the stirring time at the second stage, the pH value and the initial concentration of the humic acid solution were investigated. When the initial concentration was 10.0 mg/L, the pH value was 5.0 and the dosage of PDA was 0.2 mg/L, the removal rate could reach the maximum 94.6 %.